2002
DOI: 10.1179/135100002125000578
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of antioxidant activity of substituted pyridoindoles

Abstract: Stobadine and its two structural analogues, dehydrostobadine and N-acetylated stobadine were used to examine how structural alteration in the close proximity of the indolic nitrogen would influence the antioxidant activity of the substituted pyridoindoles. The compounds were tested for their efficiency to scavenge stable free radicals of alpha,alpha'-diphenyl-beta-picrylhydrazyl as well as for their ability to prevent 2,2'-azobis-(2-amidinopropane)hydrochloride induced peroxidation of dioleoyl phosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
6
17
0
1
Order By: Relevance
“…All compounds studied, with exception of 1-indole acetic acid, were found to have higher antiradical activity in comparison with melatonin, a 3-substituted indole derivative used as a structurally related reference antioxidant. The absence of the scavenging ability of 1-indole acetic acid is in compliance with the notion according to which the prerequisite of the antiradical activity of the indole derivatives is the presence of free hydrogen at this nitrogen (Rackova et al 2002). By its splitting, resonance stabilized indolyl radical is created, the stability of which is affected by the presence of aromatic substituents.…”
Section: Figsupporting
confidence: 73%
“…All compounds studied, with exception of 1-indole acetic acid, were found to have higher antiradical activity in comparison with melatonin, a 3-substituted indole derivative used as a structurally related reference antioxidant. The absence of the scavenging ability of 1-indole acetic acid is in compliance with the notion according to which the prerequisite of the antiradical activity of the indole derivatives is the presence of free hydrogen at this nitrogen (Rackova et al 2002). By its splitting, resonance stabilized indolyl radical is created, the stability of which is affected by the presence of aromatic substituents.…”
Section: Figsupporting
confidence: 73%
“…In the ethanolic solution, trolox scavenged 1,1`-diphenyl-2-picrylhydrazyl (DPPH) radical more efficiently than did stobadine, based on the initial velocity measurements (Rackova et al, 2002). The finding was corroborated by the respective rate constants (Rackova et al, 2004) as shown in Table 2.…”
Section: Antioxidant Efficacies In Various Assay Systemssupporting
confidence: 67%
“…Indeed, Steenken et al (1992) in their pulse radiolytic study demonstrated the ability of trolox to recycle stobadine from its one-electron oxidation product, to give a corresponding trolox phenoxyl radical. When stobadine and trolox were present simultaneously in oxidatively stressed liposomes, trolox spared stobadine in the system in a dose-dependent manner (Rackova et al, 2002). Direct interaction of trolox with the stobadinyl radical resulting in the recovery of parent stobadine molecule appears to be a plausible mechanism.…”
Section: Stobadine Troloxmentioning
confidence: 98%
See 1 more Smart Citation
“…[5][6][7] Modification of the stobadine molecule by aromatic electron-donating substitution was reported to enhance the intrinsic free radical scavenging activity, while variations of the N2 substituent afforded a synthetically accessible way to modulate the biological availability by affecting both lipophilicity and basicity of the molecule, without changing significantly the free radical scavenging activity. [5][6][7] Among the novel derivatives, the compound (±)-cis-8-methoxy-2,3,4,4a,5,9b-hexahydro-1H-pyrido [4,3-b] indole-2-carboxylic acid ethyl ester (SMe1EC2) (Fig. 1) has been subject of extensive preclinical studies.…”
Section: Introductionmentioning
confidence: 99%